Advances in FePt-involved nano-system design and application for bioeffect and biosafety. Issue 3 (24th December 2021) - Hu, Zunfu; Wei, Qiulian; Zhang, Huimin; Tang, Weina; Kou, Yunkai; Sun, Yunqiang; Dai, Zhichao; Zheng, Xiuwen
Abstract : The rapid development and wide application of nanomaterial-involved theranostic agents have drawn surging attention for improving the living standard of humankind and healthcare conditions. Abstract : The rapid development and wide application of nanomaterial-involved theranostic agents have drawn surging attention for improving the living standard of humankind and healthcare conditions. In this review, recent developments in the design, synthesis, biocompatibility evaluation and potential nanomedicine applications of FePt-involved nano-systems are summarized, especially for cancer theranostic and biological molecule detection. The in vivo multi-model imaging capability is discussed in detail, including magnetic resonance imaging and computed tomography. Furthermore, we highlight the significant achievements of various FePt-involved nanotherapeutics for cancer treatment, such as drug delivery, chemodynamic therapy, photodynamic therapy, radiotherapy and immunotherapy. In addition, a series of FePt-involved nanocomposites are also applied for biological molecule detection, such as H2 O2, glucose and naked-eye detection of cancer cells. Ultimately, we also summarize the challenges and prospects of FePt-involved nano-systems in nanocatalytic medicine. This review is expected to give a general pattern for the development of FePt-involved nano-systems in the field of nanocatalytic medicine and analytical determination.